Sector footprints in occlusion: when and how? - Bouabid, Morchad (Eastern Journal of Medical Sciences, 2019)
For the sake of saving time and material, sectoral impressions are used to record the prepared tooth, the adjacent teeth and the antagonistic teeth in occlusion. The occlusion sectoral impression technique is recognized as a precise and easy fast technique for inlays, onlays, unitary crowns or small bridges. The synergy of new fast-setting impression material with adapted impression gates is the key to the success of this technique.